Patterns of service contacts for children who have experienced maltreatment and are known to social services: a Linked Routine Administrative Data Study in Wales, England and Denmark - Bandyopadhyay, Amrita; Kennedy, Natasha; Cowley, Laura; Fallesen, Peter; Broccia, Marcella; Græsholt-Knudsen, Troels; Luna, Eliazar; Quantin, Catherine; Brophy, Sinead (International Journal of Population Data Science, 2026)
Maltreated children may have multiple contacts with services both before and after possible identification by social services. This study examines contact patterns and pathways through public services among maltreated children who are known to social services, providing evidence about potential gaps in support. This study is part of the European Commission Horizon Health 2024 SERENA project. We link children recorded in child protection (CP) and children looked after (CLA) registers in Wales, England (Growing up in England and ECHILD) and in Denmark with their routine administrative data on health (hospital admissions, emergency care, general practice), education, employment and justice. This enables comparison of public service utilisation between children known to social services and a propensity-matched cohort not known to social services, from two years before to two-ten years after social service involvement. Result Findings will be presented by each country to examine whether consistent service contact patterns can help to identify maltreated or high-risk children, along with the pattern of service usage after the initial social service contact. Preliminary findings from Wales indicate that children on the CP register, but not CLA, use emergency departments more than the matched general population. Furthermore, CLA are more likely to depend on benefits and experience unemployment in adulthood compared to matched children and those on the CP register. Mapping service usage among maltreated children can inform targeted interventions to mitigate adverse outcomes and support early identification to prevent further harm, with potential for cross-national learning.